DINAMIKA KEHIDUPAN TAYUB ATAU TAYUBAN DALAM MASYARAKAT DAN KEBUDAYAAN INDONESIA - JAWA - - Darmoko (JURNAL IKADBUDI, 2013)
Tayub or tayuban widespread until at least four provinces, namely Central Java, East Java, West Java, and Yogyakarta Special Region. Based on the type of rhythm, nuance, or character, consisting of  tayub grengseng (angkleng), tayub grengseng (arum manis), tayub grengseng (kijing miring), tayub grengseng (ketawang puspawarna),  tayub jepon (gunungsri),  tayub jepon (wolu-wolu), tayub jepon (cao glethak), tayub si Kucing, tayub Surobayan, tayub tawang mangu, and  tayub suwe ora jamu. This article trying outlines how the dynamics of life tayub or tayuban in Indonesia especially Java today.The art of dance in tayub regarding how a character speaks, being, and acting in conjunction with another character in a performance. Space dimensions concerning symmetry, asymmetry, balance, variety, contrast, and protrusion while the time dimension    associated with rhythm, aritme, tempo, and also balance, variety, contrast, and protrusion. As well as the dance performances, tayub or tayuban require reference aesthetic value: sem, nges, greget, and banyol. Arrangement of makeup and fashion shaped in such a way that the actor can portray a certain character in art tayub. Structuring the lights and the stage is a unity that creativity coordinated with other aspects of the firm, so that the stage had been set in accordance with the scene shown (right background).The results of the discussion of  "Dynamics of Life Tayub or Tayuban  in Society and Culture of Indonesia - Java" can be formulated as follows: ( 1 ) Art tayub or tayuban still has powerful functions, positive, constructive towards Indonesian society, especially in Java; (2 ) Art tayub up now has a function, either as a means of ritual ( ceremony ), vows or nadar, togetherness, education, communication, and entertainment; ( 3 ) Necessary raising funds good effort from central and local government as well as private sectors to support conservation efforts tayub or tayuban the art performed both at the sanggar and perwadahan; ( 4 ) the existence tayub or tayuban art scattered in various provinces, both in West Java, Central Java, East Java, and Yogyakarta Special Region is the wealth of local arts flourish in Indonesia. Keywords : dynamics, tayuban, Java